Subclinical Left Ventricular Longitudinal and Radial Systolic Dysfunction in Children and Adolescents with Type 1 Diabetes Mellitus - Altun, Gürkan; Babaoğlu, Kadir; Binnetoğlu, Köksal; Özsu, Elif; Yeşiltepe Mutlu, Rahime G.; Hatun, Şükrü (Echocardiography (Mount Kisco, N.Y.), 2016)
Introduction: There are few studies of subclinical systolic dysfunctions in children and adolescents with type 1 diabetes mellitus (DM), and so the available data are limited. The aim of this study was to determine early echocardiographic signs of LV systolic dysfunction in children and adolescents with type 1 DM using two‐dimensional speckle tracking echocardiography (2DSTE). Material and Methods: The study included 84 children and adolescents with type 1 DM and 32 sex‐, age‐, and body mass index–matched healthy subjects. The LV functions were assessed using conventional echocardiography, tissue Doppler imaging, and 2DSTE. Results: The results showed LV diastolic dysfunction as reflected by significantly increased A‐wave velocity, decreased E/A ratio, and increased early filling deceleration time in the patients with diabetes (P = 0.02, P = 0.029, and P = 0.04; respectively). Compared with the control group, patients with diabetes showed significantly lower values for longitudinal systolic strain and strain rate in most segments of the LV; for radial strain values of the LV; for lateral circumferential strain and posterior and anterolateral circumferential strain rate of the LV; and for global longitudinal and radial strain of the LV. Global longitudinal and radial strain values of the LV were significantly lower among patients with poor glycemic control than in the control group. Conclusion: In addition to diastolic dysfunction, LV longitudinal and radial function was found to be impaired in asymptomatic children and adolescents with type 1 DM who have normal LV ejection fraction by 2DSTE. Glycemic control may be the main risk factor for alteration of myocardial function.